Centered : Autism, Basketball, and One Athlete's Dreams - Ianni, Anthony; Keast, Rob (Book collections on Project MUSE., 2021)
""They don't know me. They don't know what I'm capable of." Diagnosed with pervasive developmental disorder, a form of autism, as a toddler, Anthony Ianni wasn't expected to succeed in school or participate in sports, but he had other ideas. As a child, Ianni told anybody who would listen, including head coach Tom Izzo, that he would one day play for the Michigan State Spartans. Centered: Autism, Basketball, and One Athlete's Dreams is the firsthand account of a young man's social, academic, and athletic struggles and his determination to reach his goals. In this remarkable memoir, Ianni reflects on his experiences with both basketball and the autism spectrum. Centered, an inspirational sports story in the vein of Rudy, reveals Ianni to be unflinching in his honesty, generous in his gratitude, and gracious in his compassion. Sports fans will root for the underdog. Parents, teachers, and coaches will gain insight into the experience of an autistic child. And everyone will triumph in the achievements of Centered"--